Ordinary Badness in Aristotelian Ethics: A Virtually Forgotten Question - Mestre, Carles José (Studia z Historii Filozofii, 2022)
In this paper, we aim to show the way in which a kind of moral badness, what we call ordinary badness, could be understood from Aristotelian ethical writings. First, we document the recognition of this type of badness in the Aristotelian source, which is seen in his presentation of “hoi polloi” (the Many). In particular, it is shown that “hoi polloi” are “phauloi”, one of the (specific) predicates that Aristotle uses to refer to moral badness. Secondly, we highlight the methodological function of “hoi polloi” in the description of incontinence and self-indulgence, and we show how the Many could be considered as a new class within the question of moral effort. Finally, and related to the result of the previous analysis, we document what could be an aporia in the Aristotelian description of the population of the polis, which brings us to join Ian Morris in his global understanding of Aristotelian political philosophy.